OPTIMIZATION OF THE USE OF POC JADAM FERTILIZER, PGPR WITH RICE HUSK BIOCHAR PLANTING MEDIA ON GROWTH RESULTS OF PEANUTS (Arachis hypogeae) - Hasmariyanti; Eka Sudartik; Ahmad Zailan (Universitas Veteran Bangun Nusantara, 2026)
This study aimed to determine the effect of Jadam Liquid Organic Fertilizer (Jadam POC) and Plant Growth-Promoting Rhizobacteria (PGPR) combined with rice husk biochar as a growing medium on the growth and yield of peanut (Arachis hypogaea L.). The study was conducted from April to June 2025 in a plantation area located in Kahu District, Bone Regency. The experiment was arranged using a Randomized Block Design (RBD) consisting of four treatments: P0 (control), P1 (87 g rice husk biochar), P2 (150 ml Jadam POC + 87 g rice husk biochar), and P3 (150 ml PGPR + 87 g rice husk biochar), with five replications, resulting in 20 experimental units. The observed parameters included plant height, number of leaves, number of pods, and pod weight. Data were analyzed using Analysis of Variance (ANOVA), and significant differences among treatments were further tested using the Honestly Significant Difference (HSD) test at the 5% significance level. The results showed that treatment P3 (150 ml PGPR + 87 g rice husk biochar) produced the best response in almost all observed parameters. The highest plant height (39.16 cm) and number of leaves (179 leaves) were obtained in P3, which were significantly higher than those in P0 and P1, but not significantly different from P2. The highest number of pods was recorded in P3 (38 pods) and was not significantly different from P2 (34 pods), although both treatments outperformed P1 and P0. The highest pod weight was also obtained in P3 (380.3 g), which was significantly different from P0 and P1 but not significantly different from P2. Therefore, the application of PGPR combined with rice husk biochar was the most effective treatment for improving the growth and yield of peanut plants. Keywords: Jadam POC, PGPR, peanut productivity, rice husk